LITERATUR REVIEW DUKUNGAN KELUARGA DALAM KEPATUHAN DIET PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISA - Sherly Widianti sherly (Jurnal Kesehatan dan Pembangunan, 2023)
Background : Dietary compliance is a treatment to maintain kidney function continuously with the principles of low-salt low protein in which the patient must take the time needed to undergo treatment. The diet that is carried out aims to prevent edema and cardio vascular complications. purposes : Untuk menganalisis hasil penelitian dukungan keluarga dalam kepatuhan diet pada pasien gagal ginjal kronik yang menjalani hemodialisa. Method: This type of research is a literature review. The criteria for the articles / research results used in this study consisted of 5 articles / research results published online between 2015-2019. The article or research results are available in full text for the researcher to use as data for analysis. Result: Based on research conducted by experts regarding family support in dietary adherence in chronic renal failure patients undergoing hemodialysis, the results show that there are four forms of family support, namely emotional support, reward support, informational support and instrumental support. Where the results obtained show that family support greatly affects dietary compliance. This is due to a lack of knowledge about the patient's diet, lack of attention from the family with busy reasons and lack of attention. Conclusion: From the 5 journal data used by researchers, it can be concluded that family support greatly affects dietary compliance. This is caused by the lack of knowledge about the diet of patients, the lack of attention from families with busy reasons and lack of information from medical personnel. Suggestion: To increase family support for compliance with recommended diet for health workers and their families to provide information, care and support to patients in the diet therapy.